Implementasi Penggunaan Forensik Digital dalam Penyelidikan dan Penyidikan Tindak Pidana di Polres Wajo - Ismail Ali; Yustiana; Kadir, Rusdi; Heriyanti; Besse Nur Fatimah (Legal Journal of Law, 2025)
Digital forensics is the use of analytical and investigative techniques to identify, collect, examine, and store evidence or information stored or encoded on a computer or digital storage media as part of valid evidence in a crime. Digital forensics can also be defined as the application of information science and technology aimed at proving a crime or proving a crime. This action is carried out by a computer device to obtain digital evidence that can be used to catch the perpetrator of the crime. To discuss this research, the problem is proposed: How is the implementation of the use of digital forensics in the investigation and investigation of criminal acts at the Wajo Police? What are the obstacles that occur in the application of digital forensic technology in the investigation and investigation of criminal acts at the Wajo Police and the efforts made to overcome these obstacles. This study uses a qualitative empirical data analysis technique method, meaning that the data analysis in this study is based on data that researchers have collected non-numerically to understand the phenomenon. The phenomena and facts obtained are based on concrete data obtained in empirical research. Research Results Based on the review of the development of human civilization above, it is known that along with the development of the era, technological science is developing rapidly. The development of computer and internet technology has an impact on the arrangement and regulation of cyber law as well as on the development of crime in cyberspace.